Perencanaan RENSTRA Sebagai Pedoman Dalam Pengelolaan Perpustakaan (Studi Kasus Perpustakaan Pusat Studi Sosial Asia Tenggara (PSSAT) Universitas Gadjah Mada Yogyakarta) - Ade Nufus, Ade Nufus (LIBRIA, 2018)
The Center for Social Studies of Southeast Asia (PSSAT) Gadjah Mada University of Yogyakarta is a library of PSSAT institutions. The library currently has more than 5,000 collection collections on Southeast Asian issues, deposit collections from PSSAT research institutes and European, Arabic and Javanese manuscripts. The library is currently managed by a librarian under the responsibility of the PSSAT agency. Currently, library activities include collection acquisition, collection processing, and public services. The library does not have a planned purpose and does not have a work program to develop the library for the better. Thus, the object of research in this paper is RENSTRA as a guide in library management. PSSAT libraries in its management have not yet referred to the guidelines. Therefore, it is deemed necessary to draw up a library strategic plan for libraries to have a clear vision and mission, targeted work program, and solutions to problems faced so that libraries have a reference and guidance in their management. The method used in this research through case study approach. After the investigation found the result that the management of PSSAT libraries have not been guided and do not even have a library strategic plan. This will have an impact on the slow progress of the library development movement, as well as the lack of library activities that attract the audience.